2018
DOI: 10.1111/mec.14950
|View full text |Cite
|
Sign up to set email alerts
|

The consequences of an introgression event

Abstract: The spread of adaptive alleles is fundamental to evolution, and in theory, this process is well-understood. However, only rarely can we follow this process-whether it originates from the spread of a new mutation, or by introgression from another population. In this issue of Molecular Ecology, Hanemaaijer et al. (2018) report on a 25-year long study of the mosquitoes Anopheles gambiae (Figure 1) and Anopheles coluzzi in Mali, based on genotypes at 15 single-nucleotide polymorphism (SNP). The species are usually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The effect of associative overdominance is strongest in low recombination regions, including inversions[78]. The balance between alleles and allelic combinations providing favourable phenotypic characters and the strength of selection against incompatibilities determine what introgression tracts will be inherited from which parent species upon hybridization (Fig 3)[21][79][80]. An insecticide resistance region was retained following a hybridization event in Anopheles coluzzi [21], suggesting a role for selection in maintaining favourable introgressed regions.…”
Section: Stabilization Of Hybrid Genomesmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of associative overdominance is strongest in low recombination regions, including inversions[78]. The balance between alleles and allelic combinations providing favourable phenotypic characters and the strength of selection against incompatibilities determine what introgression tracts will be inherited from which parent species upon hybridization (Fig 3)[21][79][80]. An insecticide resistance region was retained following a hybridization event in Anopheles coluzzi [21], suggesting a role for selection in maintaining favourable introgressed regions.…”
Section: Stabilization Of Hybrid Genomesmentioning
confidence: 99%
“…Evidence from altered expression patterns in synthetic hybrids and missing gene combinations in a hybrid species also suggest that DNA-repair[49][84][88] and genes involved in mutagenesis and cancer related pathways[84] may cause incompatibilities in hybrids. Genome formation in hybrid species is shaped by selection against incompatible combinations[43][73][79].…”
Section: Stabilization Of Hybrid Genomesmentioning
confidence: 99%
“…Notably, recent studies have found that straggling and host-switching are relatively common processes in host-symbiont systems (De Vienne et al 2013;Bourguignon et al 2018;Nylin et al 2018;Doña et al 2019). Our study suggests that in a straggling/host-switching scenario, hybridization can provide further genetic variation with important ecological and evolutionary consequences (e.g., facilitating adaptation to current hosts or facilitating the colonization of new ones) (Barton 2018). Indeed, we may have found a potential recent hybridization event (i.e., the Physconelloides individual showing the highest level of introgression), though this requires further study to rule out methodological issues (e.g., wet-lab contamination).…”
Section: Discussionmentioning
confidence: 51%
“…Notably, recent studies have found that straggling and host-switching are relatively common processes in host-symbiont systems [27][28][29][30] . Our study suggests that in a straggling/host-switching scenario, hybridization can provide further genetic variation with important ecological and evolutionary consequences (e.g., facilitating adaptation to current hosts or facilitating the colonization of new ones) 31 . Indeed, we may have found a potential recent hybridization event (i.e., the Physconelloides individual showing the highest level of introgression), though this requires further study to rule out methodological issues (e.g., wet-lab contamination).…”
Section: Discussionmentioning
confidence: 85%